Using a graph grammar system in the finite element method - Strug, Barbara; Paszyńska, Anna; Paszyński, Maciej; Grabska, Ewa (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents a system of Composite Graph Grammars (CGGs)modelling adaptive two dimensional hp Finite Element Method (hp-FEM) algorithms with rectangular finite elements. A computational mesh is represented by a composite graph. The operations performed over the mesh are defined by the graph grammar rules. The CGG system contains different graph grammars defining different kinds of rules of mesh transformations. These grammars allow one to generate the initial mesh, assign values to element nodes and perform h- and p-adaptations. The CGG system is illustrated with an example from the domain of geophysics.
Keywords: graph grammar system; automatic hp adaptivity; Finite Element Method (FEM)